Crystal structures and Hirshfeld surface analyses of bis[N,N-bis(2-methoxyethyl)dithiocarbamato-κ2 S,S′]di-n-butyltin(IV) and [N-(2-methoxyethyl)-N-methyldithiocarbamato-κ2 S,S′]triphenyltin(IV) - Mohamad Rapidah,; Awang Normah,; Kamaludin Nurul Farahana,; Jotani, Mukesh M.; Tiekink, Edward R. T. * (2018)
The crystal and molecular structures of the two title organotin dithiocarbamate compounds, [Sn(C4H9)2(C7H14NO2S2)2], (I), and [Sn(C6H5)3(C5H10NOS2)], (II), are described. Both structures feature asymmetrically bound dithiocarbamate ligands leading to a skew-trapezoidal bipyramidal geometry for the metal atom in (I) and a distorted tetrahedral geometry in (II). The complete molecule of (I) is generated by a crystallographic twofold axis (Sn site symmetry 2). In the crystal of (I), molecules self-assemble into a supramolecular array parallel to (101) via methylene-C—H...O(methoxy) interactions. In the crystal of (II), supramolecular dimers are formed via pairs of weak phenyl-C—H...π(phenyl) contacts. In each of (I) and (II), the speciﬁed assemblies connect into a threedimensional architecture without directional interactions between them. Hirshfeld surface analyses conﬁrm the importance of H...H contacts in the molecular packing of each of (I) and (II), and in the case of (I), highlight the importance of short methoxy-H...H(butyl) contacts between layers.